BICYCLE TOURISM IN COUNTY OF ŠIBENIK-KNIN - Darijo Šego; Ana-Mari Poljičak; Martina Ljubić Hinić (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
Cycling or Cyclo tourism is one of the growing forms of tourist activities. The main motive to travel for cyclists is active or passive participation in cycling, and additional motives that affect demand are participation in competitive cycling and observation of cycling events. Bicycle tours are becoming increasingly popular in European countries and the economic contribution of cycling tourists has ensured that cycling tourism has a significant place in tourism revenue. Tourists on bicycles can be an ideal tourist market for rural and peripheral areas that often lack a large offer of tourist infrastructure. Cycling tourism offers special opportunities for rural areas where this form of tourism can create and/or retain jobs and enrich the tourist offer. Attractive and diverse natural environment, rich cultural and historical heritage, favorable climate, proximity to large markets, good transport links, poorly used macadam roads, and forest roads unburdened by hiking and mountaineering demand, provide the Republic of Croatia and the County of Šibenik-Knin with many advantages for the development of this form of tourism.